Supramolecular β-sheet suckerin–based underwater adhesives - Deepankumar, Kanagavel (2020)
Nature has evolved several molecular strategies to ensure adhesion in aqueous environments, where artificial adhesives typically fail. One recently unveiled molecular design for wet-resistant adhesion is the cohesive cross-beta structure characteristic of amyloids, complementing the well-established surface-binding strategy of mussel adhesive proteins based on 3,4-L-Dihydroxyphenylalanine (Dopa). A family of structural proteins that self-assemble into cross beta-sheet networks are the suckerins discovered in the sucker ring teeth of squids. Here, we shed light on the wet adhesion of cross-beta motifs by producing recombinant suckerin-12, naturally lacking Dopa, and investigating its wet adhesion properties. Surprisingly, the adhesion forces measured on mica are as high as ca. 70 mN m-1, exceeding those measured for all mussel adhesive proteins to date. The pressure-sensitive adhesion of artificial suckerins is largely governed by their cross-beta motif, as evidenced using control experiments with disrupted cross-beta domains that result in almost complete loss of adhesion. We also incorporate Dopa in suckerin-12 using a residue-specific incorporation strategy that replaces Tyrosine with Dopa during expression in Escherichia coli. Although the replacement does not increase the long-term adhesion, it contributes to the initial rapid contact and enhances the adsorption onto model oxide substrates. Our findings suggest that suckerins with supramolecular cross-beta motifs are promising biopolymers for wet-resistant adhesion